Implementation of Online Prostitution Crime Investigation in Polres Cirebon City Jurisdictions - Arif Zaenal Abidin (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
Online prostitution is prostitution or activities that make a person as an object to be traded through electronic or online media, the media used, such as Whatsapp and other applications. In other words, here the people those who are responsible to be able to respect the norms and values embodied in the lives of people for cases of online prostitution can destroy the future of the nation in case they were found with offenders who are still teenagers and the lack of regulation of traction. Regulations invitation to entrap prostitutes. In this research, the author uses socio-juridical namely the review of secondary data in the form of legislation, as well as the outcome of legal scholars, such as books related to the subject matter to then proceed with research on primary data (obtained directly from the respondents). From the research problem, there are two things that can be inferred. Law enforcement against criminal acts of online prostitution in Polres Cirebon City Jurisdictions has been running and has conducted a series of investigative actions and investigations to unravel the cases of online prostitution. From the results of investigations conducted by the Police Cirebon Resort know that the perpetrators of online prostitution utilize Whatsapp. Building partnerships with the wider community partnerships in the wider community to help hack into your account - an account associated with seller of “young women” through online media. Suggestions in this research are; The first law enforcement against criminal acts of online prostitution by Polres Cirebon should be more intensive and thorough, because online prostitution is spreading very fast and the activities or transactions done through electronic media that police had difficulty in finding evidence and the investigation process difficult. Secondly, the hope that more people concerned about this online prostitution activities to facilitate the Polres Cirebon in overcoming it.Keywords: Law Enforcement; Criminal Act; Online Prostitution.